PENGARUH KEGIATAN OUTBOND TERHADAP KEMAMPUAN MOTORIK KASAR ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 1 PEKANBARU - Putri, Rima Irda; Chairilsyah, Daviq; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of outbound activity towards gross motor skill of children aged 5-6 years in TK Negeri Pembina 1 Pekanbaru. The method of this research used experimental method with using one group pre-test post-test design. The samples used in this study were 15 students. The data collection technique used is observation. Technique of data analysis used t-test by using program of SPSS 20. The research hypothesis was to find the influence of outbound activity towards gross motor skill of children aged 5-6 years in TK Negeri Pembina 1 Pekanbaru. Based on data analysis was known that tcalculated = 13,315 > ttable = 2,145 with Sig. (2-tailed) = 0.000. Because Sig < 0,05 it can be concluded that there is difference of gross motor skill that was be done before and after the activity of outbond. It can be interpreted that there is influence of activity towards gross motor skill of children aged 5-6 years in TK Negeri Pembina 1 Pekanbaru significant that is equal to 57,22%. Keyword: Gross motor skill, Outbond activity